PERAN BUDAYA SEKOLAH POSITIF DALAM MENCEGAH PERUNDUNGAN DI LINGKUNGAN PENDIDIKAN : SCOPING REVIEW - Samuel Hutabarat, Justin; Stephen, Stephen; Tan, Elbert; Darrel Frans, Nathanael; Mafaza, Frisia; Tji Beng, Jap (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Bullying is a serious problem in educational settings that significantly affects adolescents’ psychological, social, and academic well-being. A preventive approach based on positive school culture is considered more sustainable than reactive interventions that focus solely on case handling. This study aims to map forms of interventions and bullying prevention strategies grounded in positive school culture and to identify factors that support their effectiveness. This study employed a scoping review approach following the PRISMA-ScR guidelines and the PCC (Population, Concept, Context) framework. A literature search was conducted across several scientific databases for articles published between 2020 and 2025 in Indonesian and English. After identification, screening, and full-text review processes, 16 articles met the inclusion criteria and were analysed using a descriptive-thematic approach. The synthesis findings indicate that a positive school culture emphasizing changes in social norms toward aggressive behaviour, strengthening empathy and social responsibility values, active teacher involvement as mediators, consistent anti-bullying policies, and collaboration between schools and parents contributes to reducing bullying prevalence. School-based programs such as KiVa and the Olweus Bullying Prevention Program have proven more effective when implemented comprehensively, supported by teacher training, and accompanied by systematic school supervision. It can be concluded that establishing a positive school culture through the internalization of prosocial values, reinforcement of school policies, enhancement of teacher competence, and transformation of collective student norms represents a systemic and sustainable preventive approach to reducing bullying and fostering a safe and healthy educational environment for all students. ABSTRAK Perundungan (bullying) merupakan permasalahan serius di lingkungan pendidikan yang berdampak signifikan terhadap kesejahteraan psikologis, sosial, dan akademik remaja. Pendekatan preventif berbasis budaya sekolah positif dipandang lebih berkelanjutan dibanding intervensi reaktif yang hanya berfokus pada penanganan kasus. Penelitian ini bertujuan untuk memetakan bentuk intervensi dan strategi pencegahan perundungan berbasis budaya sekolah positif serta mengidentifikasi faktor-faktor yang mendukung efektivitasnya. Penelitian ini menggunakan pendekatan scoping review dengan pedoman PRISMA-ScR dan kerangka PCC (Population, Concept, Context). Pencarian literatur dilakukan pada beberapa basis data ilmiah untuk artikel yang diterbitkan pada tahun 2020–2025 dalam bahasa Indonesia dan Inggris. Setelah melalui tahap identifikasi, penyaringan, dan telaah teks penuh, diperoleh 16 artikel yang memenuhi kriteria inklusi dan dianalisis secara deskriptif-tematik. Hasil sintesis menunjukkan bahwa budaya sekolah positif yang menekankan perubahan norma sosial terhadap perilaku agresif, penguatan nilai empati dan tanggung jawab sosial, keterlibatan aktif guru sebagai mediator, kebijakan anti-perundungan yang konsisten, serta kolaborasi antara sekolah dan orang tua berkontribusi dalam menurunkan prevalensi perundungan. Program berbasis sekolah seperti KiVa dan Olweus terbukti lebih efektif ketika diimplementasikan secara menyeluruh, didukung pelatihan guru, dan disertai pengawasan lingkungan sekolah yang sistematis. Dapat disimpulkan bahwa pembentukan budaya sekolah positif melalui internalisasi nilai prososial, penguatan kebijakan sekolah, peningkatan kompetensi guru, dan perubahan norma kolektif siswa merupakan pendekatan preventif yang sistemik dan berkelanjutan dalam mencegah perundungan serta membangun iklim pendidikan yang aman dan sehat bagi seluruh peserta didik.